The Empire Is Dead, Long Live the Empire! Values and Human Interactions 90 Years after the Fall of the Habsburg Empire - Sascha O. Becker; Katrin Boeckh; Christa Hainz; Ludger Woessmann (Verein für Socialpolitik, 2010)
Do Empires affect human values and behavior long after their demise? In several Eastern European countries, communities on both sides of the long-gone border of the Habsburg Empire have been sharing common formal institutions for 90 years now. We exploit this geographic discontinuity in a regression-discontinuity design with country fixed effects using data of individuals living inside a restricted band around the former border. We find that historical Habsburg affiliation increases current social capital and trust and reduces corruption in several public services. Past formal institutions can leave a legacy through cultural norms even after generations of common statehood.
Keywords: N33; D73; Z10; 330; Institutions; social capital; trust; corruption; Habsburg Empire; regression discontinuity